2017
DOI: 10.18805/ijar.v0iof.8461
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of castrated Bovine reveals the characters of protein accumulation

Abstract: RNA-Seq, a new developing high-throughput sequencing technology in recent years, provides a new and more effective method for research in the genes' expression. The technology has been used to further improve our understanding on the function of the gene structure information and excavate the new transcripts and new genes. In this study, RNA-seq was employed to study the changes of the proteins after castration in cattle. The results showed the differential expression proteins between castrated cattle and nonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…In collaboration with our research team, the genes encoding for acetyl-CoA carboxylase and apolipoprotein A1 were found to be key for lipid metabolism (Wang et al, 2017a). In addition, DEGs as a result of castration were shown to be involved in immunity, lipid and fatty acid metabolism and protein synthesis (Wang et al, 2017b). Looking at the candidate genes regulating the marbled meat texture, as identified in the current study, it was concluded that their gene expression may have been determined by a variety of factors including castration and the part of the Angus cattle.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In collaboration with our research team, the genes encoding for acetyl-CoA carboxylase and apolipoprotein A1 were found to be key for lipid metabolism (Wang et al, 2017a). In addition, DEGs as a result of castration were shown to be involved in immunity, lipid and fatty acid metabolism and protein synthesis (Wang et al, 2017b). Looking at the candidate genes regulating the marbled meat texture, as identified in the current study, it was concluded that their gene expression may have been determined by a variety of factors including castration and the part of the Angus cattle.…”
Section: Discussionmentioning
confidence: 96%
“…The expression of the protein-coding genes cytochrome P450, family 1, subfamily A, polypeptide 1 (CYP1A1) and Ras-related Associated with Diabetes (RRAD) was significantly increased in muscle fat of high marble level as compared to low marbled meat (|log2-fold change|= 2.09, |log2-fold change| = 1.90). Previous studies suggested that cytochrome P450, family 21, subfamily A, polypeptide 2 (CYP21A2) of the cytochrome P450 family is involved in the synthesis of cholesterol (Wang et al, 2017b), steroids and other lipids, and that CYP1A1 may also be involved in lipid synthesis. The CYP1A family is mainly involved in the metabolism of polycyclic aromatic compounds and aromatic amines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IMF is distributed in skeletal muscle, and there is a positive correlation between IMF content and meat tenderness (Houbak et al, 2008;Magnabosco et al, 2016). It is well known that peroxisome proliferator-activated receptor gamma (PPARγ) is a member of the transcription factor nuclear receptor superfamily, which is a critical regulator of adipogenesis, glycolipid metabolism and cell proliferation and differentiation (Kersten et al, 2000;Wang et al, 2017). PPARγ is not only a regulator of adipose tissue development, but also modulates a variety of genes expression involved in fatty acid transport and metabolism at the transcriptional level (Freitag and Miller, 2014).…”
Section: Introductionmentioning
confidence: 99%